Securing soils in a changing climate: A soil route map for Scotland - Buckingham, Sarah; Baggaley, Nikki (SAC Consulting, part of Scotland’s Rural College, 2025)
There are many risks threatening Scottish soils across different soil types and land covers. However, unlike air and water, there is no single overarching soil policy providing security and governance for Scottish soils. Soils are spread across multiple policy divisions, which results in a lack of cohesive leadership in tackling threats to soils. The aim of this route map is to consolidate the challenges of managing soil systems to develop an overarching strategy for delivering improved soil security across Scottish landscapes.
Keywords: soil health; climate change; Scotland; soil systems; governance